Scientific opinion on the safety of a proposed amendment of the conditions of use of the food additive sorbitan monostearate (E 491) in enzyme preparations - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Lourdes Bastos; Polly Boon; Biagio Fallico; Reginald FitzGerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal, 2025)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF Panel) provides a scientific opinion on the safety evaluation of a proposed amendment of the conditions of use of the food additive sorbitan monostearate (E 491) in accordance with Annex III, Part 3 to Regulation (EC) No 1333/2008, with respect to the intended use as a food additive in preparations of the food enzyme asparaginase (also known as acrylamide reducing yeast, or ARY). The group of sorbitan esters (E 491–495) was re‐evaluated by the EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS Panel) in 2017. The ANS Panel established a group ADI of 10 mg sorbitan/kg body weight (bw) per day applicable to the food additives E 491–495. In the present opinion the Panel calculated an updated dietary exposure estimate of sorbitan resulting from the current authorised uses of the group of sorbitan esters (E 491–495), and from the proposed amendment of the conditions of use of sorbitan monostearate (E 491) in enzyme preparations. In updating the dietary exposure with the latest dietary surveys available, the group ADI of 10 mg sorbitan/kg bw per day was exceeded in toddlers and children at the 95th percentile in the refined non‐brand loyal scenario for a limited number of dietary surveys. This observation holds true either considering the proposed amendment of the conditions of use of the food additive E 491 or only the currently permitted uses in the exposure calculations. The same conclusions apply to the dietary exposure estimates for consumers of food supplements, for which the ADI is exceeded in children at the 95th percentile. The Panel however concluded that the conservative assumptions made in the refined scenarios have resulted in a clear overestimation of the dietary exposure and therefore that the calculated exceedance of the acceptable daily intake (ADI) is not of safety concern. The Panel concluded that the proposed amendment of the conditions of use of sorbitan monostearate (E 491) in preparations of the food enzyme ARY has little impact on the current dietary exposure to sorbitan resulting from the already permitted uses and reported use levels of sorbitan esters (E 491–495) and would not be of safety concern.